ANALYSIS OF FACTORS AFFECTING THE INTENTION TO TRANSACT OF XYZ E-COMMERCE USERS IN JAKARTA: A STUDY OF PERCEIVED EASE OF USE, PERCEIVED USEFULNESS AND PERCEIVED RISK - Fernando, Luis; Lina, Lina (International Journal of Application on Economics and Business, 2024)
This Research aims to investigate how perceived ease of use, perceived usefulness, and perceived risk affect the intention to transact on XYZ e-commerce users in Jakarta. The research population involves XYZ e-commerce users who are in Jakarta during the period of this study, which is for 3 months from June to August 2023. The sampling technique used a non-probability sampling method with a purposive approach, involving 147 respondents. Data collection was carried out through distributing questionnaires offline and online. Data analysis was carried out using the Structural Equation Modeling (SEM) method with the Smart PLS 3.0 application. The results showed that 39.8% of the variation in the intention to transact variable could be explained by perceived ease of use, perceived usefulness, and perceived risk. The remaining 60.2% may be influenced by other factors outside the scope of this studyThe research findings also show that both perceived ease of use and perceived usefulness have a positive and significant influence, both individually and jointly on intention to transact at XYZ e-commerce in Jakarta. Meanwhile, perceived risk shows a negative and significant influence on the intention to transact on XYZ e-commerce in Jakarta.